Paradise Valley - Cramer, W. Dale (Minneapolis, Minn. : Bethany House, 2011)
Caleb Bender and other members of an Ohio Amish community decide to relocate to Mexico to avoid conflicts with Ohio's laws. Caleb's family are the first settlers. His daughters eventually connect with the local people, but the family is endangered by the strife following the Mexican Revolution.
Keywords: Amish -- Fiction; Amish teenagers -- Fiction; Frontier and pioneer life -- Fiction; Christian fiction